A Case of Choroidal and Vitreous Hemorrhage Following Micropulse Transscleral Cyclophotocoagulation. Issue 7 (July 2020) - Aldaas, Khalid M.; Brasington, Chadwick; Zhang, Alice Yang
Abstract : Choroidal hemorrhages involve bleeding into the potential space between the choroid and sclera and are a serious ocular complication. Common causes of choroidal hemorrhages include intraocular surgeries, such as scleral buckling, cataract extractions, and glaucoma filtering procedures, or trauma. We report a case of choroidal and vitreous hemorrhage after micropulse cyclophotocoagulation. An 82-year-old female presented postoperative day 1 with blurry vision and pain in her right eye. Examination showed that she had a choroidal hemorrhage, 200 degrees of ciliary body swelling, and vitreous hemorrhage. Although the choroidal hemorrhage resolved with steroids, the vitreous hemorrhage required pars plana vitrectomy. To the best of our knowledge, this article discusses the first reported case of choroidal and vitreous hemorrhage due to micropulse cyclophotocoagulation.